Trait-Level Variability in Attention Modulates Mind Wandering and Academic Achievement - Pereira, Effie J.; Gurguryan, Lauri; Ristic, Jelena (Frontiers in Psychology, 2020)
Although mind wandering remains ubiquitous in daily life, the processes that underlie and sustain this behavior remain poorly understood. Across two experiments, here, we studied the role of intrinsic temperament traits, which shape stable behavioral processes, in moderating the association between mind wandering and the real-life functional outcome of academic success. In Experiment 1, participants completed the Mind Wandering Questionnaire, the Adult Temperament Questionnaire, and reported their grade for the highest degree completed or in progress. Individuals with traits of low Effortful control, high Negative affect, and low Extraversion indicated more mind wandering. Effortful control moderated the relationship between mind wandering and academic success, with higher tendency for mind wandering associated with higher academic achievement for individuals with high Effortful control, and lower academic achievement for those with low Effortful control. Experiment 2 confirmed these links using the visual metronome response task, an objective measure of mind wandering. Together, these results suggest that the intrinsic temperament trait of Effortful control represents one of the key mechanisms behind the functional influence of mind wandering on real-life outcomes. This work places an innate ability to control attention at the very core of real life success, and highlights the need for studying mind wandering through an interdisciplinary lens that brings together cognitive, biological, social, and clinical theories in order to understand the fundamental mechanisms that drive this behavior.